2011
DOI: 10.1073/pnas.1105994108
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for a protective role of the peritrophic matrix against intestinal bacterial infection in Drosophila melanogaster

Abstract: The peritrophic matrix (PM) forms a layer composed of chitin and glycoproteins that lines the insect intestinal lumen. This physical barrier plays a role analogous to that of mucous secretions of the vertebrate digestive tract and is thought to protect the midgut epithelium from abrasive food particles and microbes. Almost nothing is known about PM functions in Drosophila, and its function as an immune barrier has never been addressed by a genetic approach. Here we show that the Drosocrystallin (Dcy) protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
246
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(257 citation statements)
references
References 38 publications
7
246
2
2
Order By: Relevance
“…Interestingly, we previously showed that A. phagocytophilum infection of Ixodes ticks reduces expression of stat, and that colonization is enhanced when stat is silenced (65); this suggests a role for the PM as a contributing factor during A. phagocytophilum infection of the tick. The glycan-rich PM layer separates the gut lumen from the epithelial cells and provides a protective barrier in arthropods against microbes and components of the incoming blood meal (66). Periodic acid-Schiff (PAS) staining of A. phagocytophilum-infected and P1-injected nymphal guts showed a significant decrease of the PM-like layer, which leads to increased PM permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we previously showed that A. phagocytophilum infection of Ixodes ticks reduces expression of stat, and that colonization is enhanced when stat is silenced (65); this suggests a role for the PM as a contributing factor during A. phagocytophilum infection of the tick. The glycan-rich PM layer separates the gut lumen from the epithelial cells and provides a protective barrier in arthropods against microbes and components of the incoming blood meal (66). Periodic acid-Schiff (PAS) staining of A. phagocytophilum-infected and P1-injected nymphal guts showed a significant decrease of the PM-like layer, which leads to increased PM permeability.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis with fluorescence-labeled lectin indicated the presence of lectin in the midgut of the digestive tracts of flies. However, we speculate that lectin did not enter the body across the wall of the tract due to the peritrophic matrix, which serves as a barrier against microbial pathogens (25). Therefore, the antiviral effects of P. vulgaris PHA do not appear to occur through a direct interaction with the virus, but by indirectly altering host responses against viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…The gut is also the major contact point for microorganisms, whether pathogens, members of the microbiota or food (dietary microbes) [21,41]. Under normal conditions, the microbiota reside in the gut lumen within the endoperitrophic space [42], which is delimited by the peritrophic matrix, a grid-like structure of chitin polymers and proteins that lines the midgut [18,43] and limits the passage of luminal contents and pathogens [44]. Another physical barrier is provided by a mucus layer, composed of polysaccharides and proteins (mucins), which is located between the peritrophic matrix and the epithelium [18].…”
Section: Drosophila Gut Physiology and Gut-associated Microbiotamentioning
confidence: 99%